Poetics of modern literature of Kazakhstan - Abisheva, Saule; Polyak, Zinaida; Serikova, Samal; Kermeshova, Zhanna; Sabirova, Dina (Opción, 2018)
Presently all art forms endure transformation and reconsideration including literature. The whole complex of social, economic, political and cult urological processes led to global changes in art of an era of postmodernism. Verbal creativity of Kazakhstan of the period of Independence endures modification of art forms. If to speak about literature of Kazakhstan, it should be noted that in Kazakhstan the national and Russian-speaking prose actively develops. The Kazakhstan literary criticism addresses the research of main tendencies of development of modern literature – the genre. In works of the latest literature of Kazakhstan demonstrates that during an era of a postmodern there are profound changes.